Aksjonsforskning I Norge, Volum 2: Grunnlagstenkning, Forskerroller Og Bidrag Til Endring I Ulike Kontekster 2020
DOI: 10.23865/noasp.121.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Aksjonsforskning – ansats til en historisk systematikk

Abstract: The following text attempts, without pretending completeness, to analyze approaches to action research based on where and how they position themselves socially, on how they work, and on their actual basic distinctions. The result is a tentative typology presented roughly historically, which cuts through the many labels typical of current action research. Different approaches are useful, each for different purposes. Still, most circle consciously or subconsciously around some form of “practice” which works as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…But such arguments are not the main reasons why conventional researchers should be interested in action 1 Further arguments and references to other authors and research literature indicating what I try to argue here are to be found in e.g. Eikeland (1985Eikeland ( , 1995Eikeland ( , 1997Eikeland ( , 1998Eikeland ( , 2001Eikeland ( , 2006aEikeland ( , 2006bEikeland ( , 2006cEikeland ( , 2006dEikeland ( , 2007aEikeland ( , 2007b. Interested readers will also find my reasons for thinking that answers to almost all the challenges raised in this text can be developed by taking seriously into account the more than 2000 years old works of Aristotle, among many others, of course.…”
mentioning
confidence: 82%
“…But such arguments are not the main reasons why conventional researchers should be interested in action 1 Further arguments and references to other authors and research literature indicating what I try to argue here are to be found in e.g. Eikeland (1985Eikeland ( , 1995Eikeland ( , 1997Eikeland ( , 1998Eikeland ( , 2001Eikeland ( , 2006aEikeland ( , 2006bEikeland ( , 2006cEikeland ( , 2006dEikeland ( , 2007aEikeland ( , 2007b. Interested readers will also find my reasons for thinking that answers to almost all the challenges raised in this text can be developed by taking seriously into account the more than 2000 years old works of Aristotle, among many others, of course.…”
mentioning
confidence: 82%
“…Educational action research consists of a broad family of complementary research approaches, strategies and methods for understanding and developing social practices within education. Since the 1950s, variants of educational action research have been developed both as a response to changing historical, cultural, social and political circumstances and with the intent to emphasise specific aims, methods or outcomes (Eikeland, 2020;Langelotz & Olin, 2022, pp. 1-2;Reason & Bradbury, 2006, p. xxii).…”
Section: On Educational Action Researchmentioning
confidence: 99%